Rancang Bangun Deteksi Alkohol Pada Urine Dengan Sensor TGS 2620 Berbasis Mikrokontroler AT89S51 - Sutanto, Heri; Haryowati, Anggraeni Dwi; Arifin, Zainal (BERKALA FISIKA, 2010)
The design of alcohol detection in urine using sensors TGS 2620 microcontroller AT89S51 has been done. This device is made with a system that is simple and affordable prices so that it can be used for police and medical laboratories. Alcohol detection in urine is done by using sensors TGS 2620, ADC and the microcontroller. Measured values of the sensor are converted by the ADC and then processed microcontroller to be processed and sent to a computer with RS 232 modules. From the results of engineering manufacture alcohol detection devices in urine obtained test results showing that an increase in the value of sensor output voltage (VRL) at the time the sensor detects the presence of alcohol and research results of alcohol in urine is shown with captions positive or negative urine samples and the percentage content of alcohol . Â  Keywords: Alcohol, Urine, Sensors TGS 2620, Microcontroller AT89S51.